Penerapan Outdoor Learning dengan Media Klinometer Terhadap Aktivitas dan Kemampuan Komunikasi Matematis Siswa - Noor Fajriah; Selfina Soraya (JRPM (Jurnal Review Pembelajaran Matematika), 2017)
This study aims to explain about students’ activities, mathematical communication skills, students’ achievement and students' responses toward the implementation of outdoor learning using clinometers through utilization of schoolyard as a learning resource on the topic of trigonometry in SMA Global Islamic Boarding School (GIBS). The method employed in this study is quasi-experimental with one shot case study. The subject of this study includes 25 female students who are in 10 grade of natural science class. The data are collected through observation, written tests, and questionnaire. Data gained are analyzed using descriptive statistic. The result indicates that: 48% of students’ activities are in the category of active and very active; the average improvement of student’s mathematical communication skills is in the high category; there are 80% of students’ achievements passed the minimum mastery criteria; the students’ responses are satisfied with the learning experience through the implementation of outdoor learning.